The Influence of Word of Mouth and Social Media Content on Livestock Purchasing Decisions Among Millennials and Gen Z in Palembang - Egi Zuhdi; Ahmad Maulana; Aslamia Rosa (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Livestock purchasing is primarily utilized to meet the demand for animal products such as meat, dairy, and wool. Livestock purchasing highly depends on the context and goals of the consumer in a generation. Some methods can be used for word of mouth. As time goes by, the existing technology is developing, so the current method of livestock purchasing has become more accessible by utilizing existing media social content. However, as a past method, word of mouth still affected consumer purchase decisions, even among millennials. This study will comprehensively examine, explore, and validate this phenomenon by examining how word of mouth and social media content influence millennial and Gen Z consumers' livestock purchasing decisions. This research was carried out from May to June 2024, and data was collected on Google from consumers who had purchased livestock (cows or goats). This research used several data processing method tests, including inferential descriptive statistics and multiple linear regression. This research uses a questionnaire distribution technique by 100 respondents directly and distributed to livestock buyers in Palembang. The scope of this research is to determine the influence between the words of mouth (x1) and variables social media content variables (x2) on the purchasing decision variable (y) for livestock in Palembang. In this research, the words of mouth variable (x1) have five dimensions: talkers, topics, tools, talking part, and tracking. The social media content variable (x2) has seven dimensions: clear, concise, concrete, correct, coherent, complete, and courteous. Furthermore, the purchasing decision variable has six dimensions: product choice, brand choice, channel choice, purchase time, purchase amount, and purchase method. The implications of these findings were discussed, and limitations and future research directions were suggested.